Crossroads of Cuisine The Eurasian Heartland, the Silk Roads and Food (Volume 2) - Buell, Paul David (Brill, 2020)
Crossroads of Cuisine provides a history of foods, and foodways in terms of exchanges taking place in Central Asia and in surrounding areas such as China, Korea or Iran during the last 5000 years, stressing the manner in which East and West, West and East grew together through food. It provides a discussion of geographical foundations, and an interlocking historical and cultural overview going down to the present day, with a comparative country by country survey of foods and recipes. An ethnographic photo essay embracing all parts of the book binds it all together, and helps make topics discussed vivid and approachable. The book is important for explaining key relationships that have not always been made clear in past scholarship.